An Adhesive Hydrogel with "Load‐Sharing" Effect as Tissue Bandages for Drug and Cell Delivery. Issue 43 (18th September 2020) - Chen, Jing; Wang, Dong; Wang, Long‐Hai; Liu, Wanjun; Chiu, Alan; Shariati, Kaavian; Liu, Qingsheng; Wang, Xi; Zhong, Zhe; Webb, James; Schwartz, Robert E.; Bouklas, Nikolaos; et al.
Abstract: Hydrogels with adhesive properties have potential for numerous biomedical applications. Here, the design of a novel, intrinsically adhesive hydrogel and its use in developing internal therapeutic bandages is reported. The design involves incorporation of "triple hydrogen bonding clusters" (THBCs) as side groups into the hydrogel matrix. The THBC through a unique "load sharing" effect and an increase in bond density results in strong adhesions of the hydrogel to a range of surfaces, including glass, plastic, wood, poly(tetrafluoroethylene) (PTFE), stainless steel, and biological tissues, even without any chemical reaction. Using the adhesive hydrogel, tissue‐adhesive bandages are developed for either targeted and sustained release of chemotherapeutic nanodrug for liver cancer treatment, or anchored delivery of pancreatic islets for a potential type 1 diabetes (T1D) cell replacement therapy. Stable adhesion of the bandage inside the body enables almost complete tumor suppression in an orthotopic liver cancer mouse model and ≈1 month diabetes correction in chemically induced diabetic mice. Abstract : An adhesive hydrogel based on a "load‐sharing" effect of triple hydrogen bonding clusters is reported. To demonstrate their potential applications, these adhesive hydrogels are engineered into internally applied tissue bandages for delivery of either antitumor drugs directly to the tumor site or insulin‐producing cells to treat type 1 diabetes.